2007
DOI: 10.1590/s0103-84782007000200041
|View full text |Cite
|
Sign up to set email alerts
|

Hospedeiros e parasitóides de Anastrepha spp. (Diptera: Tephritidae) em Itaubal do Piririm, Estado do Amapá, Brasil

Abstract: RESUMO Este trabalho foi realizado no município de Itaubal do Piririm, Estado do Amapá, com o objetivo de registrar a ocorrência de moscas-das-frutas Palavras-chave: moscas-das-frutas, índice de infestação,Amazônia. ABSTRACT The occurrence of fruit flies on three host plants and their parasitoids was registered in Itaubal do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
2
8
1
4
Order By: Relevance
“…Manilkara was already known to be a host of A. serpentina in Amapá, but without association with parasitoids (Deus et al 2009) Low parasitism rates were observed in hog plum (0.6 to 5.3%). These values are lower than those reported for the same host in the municipalities of Itaubal do Piririm (11.9%), Ferreira Gomes (21.7%), and Macapá (23.6%) , 2007a, Silva & Silva 2007). …”
Section: Fruit Fliescontrasting
confidence: 69%
See 2 more Smart Citations
“…Manilkara was already known to be a host of A. serpentina in Amapá, but without association with parasitoids (Deus et al 2009) Low parasitism rates were observed in hog plum (0.6 to 5.3%). These values are lower than those reported for the same host in the municipalities of Itaubal do Piririm (11.9%), Ferreira Gomes (21.7%), and Macapá (23.6%) , 2007a, Silva & Silva 2007). …”
Section: Fruit Fliescontrasting
confidence: 69%
“…In Laranjal do Jari, few specimens of Opius bellus and U. anastrephae and only one specimen of Doryctobracon crawfordi were collected. Doryctobracon areolatus is the most abundant braconid parasitoid of fruit flies in the State of Amapá , Silva et al 2007a, b, 2010, Deus et al 2009, and is also considered to be the most widely distributed throughout Brazil (Leonel Junior et al 1995, Canal & Zucchi 2000 and Latin America (Ovruski et al 2000). The predominance of this species compared to other native parasitoids may be associated not only with its greater ability to locate hosts, but also its ability to infest larvae at early instars (Matrangolo et al 1998).…”
Section: Fruit Fliesmentioning
confidence: 99%
See 1 more Smart Citation
“…No período do "inverno" (fevereiro a maio), é alta a disponibilidade de frutos/semente, pois corresponde ao período de frutiicação das árvores que circundam as margens do rio Araguari, tais como o taperebá (novembro a março; FREITAS et al, 2010), andiroba (março a maio; FREITAS et al, 2010;, sarão (dezembro a março, segundo os pescadores), ingá (frutos quase o ano todo, com picos em março, maio, agosto/setembro e outubro/janeiro; FALCÃO; CLEMENT, 2000;SILVA et al, 2007), seringa (agosto a maio; MAIA, 2001), jenipapo (março a junho, podendo produzir em outras épocas; MAIA, 2001) e imbaúba (fevereiro a agosto; MAIA, 2001;SALMAN et al, 2008;SILVA JÚNIOR et al, 2013). Portanto, os pacus estão consumindo recursos alimentares derivados da loresta inundada, no período que corresponde à alta disponibilidade.…”
Section: Discussionunclassified
“…striata on guava and cajá and An. antunesi on cajá in the State of Amapá(Silva et al 2007), and it was recorded in Bahia(BomÞm et al 2010). This is the Þrst record of As.…”
mentioning
confidence: 96%